THE DYNAMICS OF REGIONAL EXPANSION AND ITS IMPLICATIONS FOR PUBLIC SERVICES - Ahmat, Ahmat (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2024)
This study aims to analyze the effectiveness of regional expansion policy as an instrument to improve public services in Indonesia. The background of this research departs from the assumption that regional expansion can shorten the span of government control, accelerate development, and bring services closer to the community, but in practice it does not always produce the expected results. This research uses a qualitative-descriptive approach with literature studies, analysis of legislation, and evaluation of secondary data from the Ministry of Home Affairs and case studies of new autonomous regions (DOB). The results show that regional expansion can have positive impacts such as increased access to basic services and bureaucratic efficiency, especially if supported by adequate fiscal capacity, human resources, and infrastructure. However, there are still many DOBs that experience fiscal dependency, institutional weakness, and low public service performance due to expansion that is triggered more by local political interests than the real needs of the community.Keywords: Regional Expansion, Public Services, Decentralization